Effectiveness of implementing competency enhancement activities for Hindu religion teachers at the Denpasar Ministry of Religion Office - Ni Made, Irna Lestari; Ni Putu Tirka Widanti; I Made Kartika (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
The competency enhancement program is an effort by government agencies to improve educators' competencies. The Ministry of Religion of the Republic of Indonesia implements this program due to its role in education, particularly religious education. Enhancing the competency of Hindu religion teachers is the responsibility of the Directorate General of Hindu Community Guidance, and in Bali, it is carried out by the Denpasar Ministry of Religion Office. The implementation of competency enhancement activities for teachers in Denpasar has not been evaluated, either internally or externally by the Directorate General of Hindu Community Guidance, regarding its benefits for Hindu religion teachers. The aim of this research is to assess the effectiveness of the competency enhancement activities for Hindu religion teachers at the Denpasar Ministry of Religion Office conducted in 2023. This study is a descriptive qualitative research using purposive sampling for informant selection, with data collected through observation, interviews, and literature review. The findings show that the competency enhancement activities for Hindu religion teachers at the Denpasar Ministry of Religion Office are effective, following a process of planning, organizing, actualizing, controlling, and evaluating. Despite facing internal challenges such as inadequate facilities, budget, and human resources, and external challenges such as dual responsibilities for educational personnel and lack of teacher awareness, the program has managed to address these obstacles through efforts such as optimizing the budget implementation checklist and improving communication among staff, leaders, religious institutions, and Hindu organizations.